Teoria histórico-cultural e as Consequências da patologização da surdez na vida dos surdos: aquisição tardia da libras e dificuldades para a constituição da identidade surda. - Steffen, Lindomar Lindolfo (2022)
This paper aims identify in the academic-scientific production available on the BDTD, CAPES and SciELO platforms, since 2005 until 2020, and other academic productions, what circumstances can make the deafness be pathologized and which consequences for the sign language delayed acquisition by the deaf and for their identity constitution as deaf. It also seeks to analyze and understand the Deafness Pathologization terms, the late sign language acquisition and Deaf Identity, by the cultural-historical theory iluminated. As well as other concepts, such as: critical period, speech and language; medical and social models of disability; regular school and bilingual school; deaf community and deaf people, among others. The research is exploratory, bibliographic and qualitative, is based on the Vygotskian cultural historical theory, which displays the emergence idea for a new human psyche understanding ways, subverting the individual and society determinist and static logic. As results, the term "deafness pathologization" wasn’t found in the researched references, which shows that can be considered a neologism. It can also be considered as a resignified concept regarding the research topic, deafness as a medicalization synonym, negative attribute, or disease status. The pathologizing deafness fact, that means, understand it from a medical perspective, biologizing, highlights several negative consequences for the deaf people life, such as: late sign language acquisition or not in the critical/sensitive period; delay in language development and higher psychological functions; delay in the their identity constitution as deaf, as well as obstacle rendezvoused by the deaf in access to knowledge and culture. Other factors that could mean negative consequences were also found, such as the sign language unknowing by parents, teachers and society in general, plus insufficient public policies, which, directly or indirectly, also put obstacles in the deaf people life.